Analisis Perhitungan Harga Pokok Produksi Pada CV Rantau Bayur Permai - Indi Ramadani; Zulkifli Zulkifli; Eka Jumarni Fithri (Student Research Journal, 2023)
The author of this final report aims to analyze the calculation of the cost of production based on orders for January 2023 at CV Rantau Bayur Permai. The company is located at Jln. Palembang – Jambi, Sukamoro, Kel. Tanah Mas Kec. Talang Kelapa KM.14 sukajadi, Banyuasin Regency, South Sumatra 30961. And is a company engaged in convection. From the data obtained by the author through interviews and observations. Based on data from the company, the authors found several problems, namely the company had not classified the cost of raw materials and auxiliary materials, the company had not taken into account the cost of depreciation of equipment and electricity into the calculation of the cost of production, so that the calculation of the cost of production was not correct as a whole. Based on the existing problems, the author suggests grouping raw material costs and supporting material costs and calculating depreciation costs and electricity costs into factory overhead so that the cost of production can be calculated correctly.